Empowerment in Madrasah: What English Teachers Have to Say - Misdi, Misdi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2017)
Empowerment is often defined by impact, competence, and meaningfulness (Frymier, Shulman, & Houser, 1996). In order to empower students, English teachers have to be empowered themselves.  However, research indicates teachers of English in madrasahs  is still underperformance. Thus, this paper is attempted to explain the aspects and factors relating to empowerment issues in the contexts of the madrasahs in Indonesia. Despite of small number of madrasah that have high qualified performances in instructional practices, public madrasahs still sound unsatisfying comparing to the secular schools. The issue of teachers and learners’ voices are still lack of attention in both school and instructional decision making. As the results, participation and engagement in English learning are still remaining less appreciation in term of meaningful learning both for teachers and students. Keywords: empowerment, madrasah, decision-making, voice, meaningful learning, learning involvement